p-Adic Riesz Potential and Its Commutators on Morrey-Herz Spaces - Yanlong Shi; Yafeng Shi; Shenbao Chen (Journal of Function Spaces)
In this paper, we establish the boundedness of p-adic Riesz potential on Morrey-Herz spaces, as well as the λ-central BMO estimates for multilinear commutators of p-adic Riesz potential on Morrey-Herz spaces.